UMPSA Edutourism Programme offers learning opportunities while travelling - Nor Salwana, Mohammad Idris (UMPSA, 2024)
KUANTAN, 13 May 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) introduced the Edutourism Programme through packages specifically designed with the objective of introducing cultural diversity, language and the beauty of interesting places, especially in Pahang Darul Makmur and Malaysia in general.